Coordination in crisis: the practice of medical humanitarian emergency - Stellmach, D (2016)
This thesis in anthropology investigates how emergency is socially constituted as a named and actionable entity. Specifically, it asks how human values and techno-scientific practices contribute to the constitution of emergency in the context of medical humanitarian intervention. The study considers emergency from an ethnographic perspective, as a group of international medical humanitarian practitioners from the aid group Médecins San Frontières (MSF) come to understand and respond to the 2013 outbreak of armed conflict in South Sudan and the potential for mass starvation among certain groups within that country. Through the method of participant observation, it examines how emergency is understood or constituted at three different conceptual levels: at the level of the individual clinical encounter, the level of population statistics, and the level of political representations of crisis. By extension, it inquires as to how professional formation and moral categories determine appropriate response. The study reveals how values, ethics and conceptions of "the good" are embodied in—yet imperfectly translated through—numerical measures and institutional structures. This reveals a key paradox of medical humanitarianism: that rational, technocratic institutions simultaneously enable and debilitate the goals and means of humanitarian action. This study is based on 11 months of fieldwork (Oct 2013-Sept 2014) with the Amsterdam operational section of MSF. The fieldwork was multi-sited; it included participant observation of MSF activities in Amsterdam (The Netherlands), Juba, Leer and Bentiu (South Sudan).